Integrated Implementation of Teaching Factory and Islamic Education to Develop Learning Attitude and Work Ethics of Students in Vocational Schools - Herliana Herliana; Teuku Zulfikar; Muhammad Duskri; Muhammad Furqan (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2024)
Aceh Province, which is a Special Autonomous Region based on Islamic Sharia, based on 2021 data shows that the implementation of the Teaching Factory has not yet occurred completely in all vocational schools in Aceh. This is a strong indication that the main factor has not yet seen the outcomes expected by the community. Seeing the gap in the quality of Teaching Factory implementation among vocational schools in Aceh, it is necessary to conduct a study regarding the integration of Islamic education through the Teaching Factory model as an effort to develop learning attitude and work ethic of students in vocational schools in Aceh. The research design used is a sequential explanatory design or combination model research. The total sample for quantitative data was 228 respondents using the Structural equation Modeling analysis method. Meanwhile, for qualitative data, the sample size was 509 respondents. Quantitative data analysis uses the Structural equation Modeling analysis method, while qualitative data describes the results descriptively by linking them to existing facts and supporting theories from the results of data integration from the implementation of the Teaching Factory and Islamic Education. The research results show that teaching and learning activities in vocational schools are not just coincidental or incidental, but are part of a planned effort to integrate Islamic education into the learning system and daily life through Teaching Factory learning. This integration has a positive and holistic impact on students' personalities, skills, attitude, and values, with a focus on success in the world of business run according to Islamic principles.